Diare adalah kondisi yang ditand Ecoli Penyabab Diare Akut : Ecoli Penyabab Diare Akut: Patogenesis, Diagnosis dan Tatalaksana - Shinta Dewi, Brigitta; Soleha, Tri Umiana; Septiani, Linda; Apriliana, Ety (Medula, 2024)
The presence of Escherichia coli bacteria or what is often called E.coli is an indicator of contaminated food and water which shows that there is contamination in human feces. 16 Research results show that consuming food contaminated with Escherichia coli bacteria can cause symptoms of diarrhea, pain, fever, and vomiting6. Escherichia coli bacteria can be transmitted through contact with infected food handlers when processing food16. Escherichia coli can be transmitted from feces through contact with human fingers, flies, soil and water that comes into direct contact with food and eating utensils19. Diarrhea in Indonesia is an endemic disease and a potential disease that is associated with a significant mortality rate. In that year, there were 21 extraordinary events (KLB) which spread across 12 provinces and 17 districts/cities. 12. An increase in diarrhea occurred in 2018 with the number of cases reaching 4,504,524 people. In 2019, diarrhea cases decreased slightly to 4,485,513 people. The national incidence rate of diarrhea is 270 per 1,000 population12. In 2020, diarrhea in Bandar Lampung City reached 16,989, in 2021 there was an increase with the number of cases 22,371 (Central Statistics Agency for Bandar Lampung City, 2023) 4. Knowledge and updates regarding E. Coli as a cause of diarrhea are important for medical personnel.